An Analysis Pragmatics of Tangsi Language in The Sawahlunto Social Structural Approach - Aditiawarman, Mac; Novita, Bella (Fakultas Sastra Universitas Ekasakti, 2024)
This study is entitled An Analysis Pragmatics Of Tangsi Language in The Sawahlunto Social Structural Approach. Analyzing the background of the formation of the Tangsi language. and its function in society. Finding the meaning of the Tangsi language by using the locutions and illocutions used by the Tangsi people themselves. Knowing that Tangsi Language in Speech Acts influences the social structure of people with different cultures. This research uses descriptive qualitative research. The data in this study are locutinary and illocutionary speech of the Tangsi people who use the Tangsi language. The targets were the Tangsi people who were descendants of the chain people from the Dutch era. Researchers used several methods to collect data in this study, namely observation, field notes, recording speech acts used by the Tangsi community which are used as research objects in everyday conversation and expressing them contain a sociocultural approach. Researcher found that socio-cultural has a very large impact on the speech acts of society, especially when people who are chained come from various regions so that they can create a new language in their work environment or prison environment. The Tangsi people still use the Tangsi language to this day when communicating with other Tangsi people, but there are also people from Minang backgrounds who can also speak the Tangsi language. The researcher is one of the Tangsi people, but so far researcher have not known the difference between Tangsi and Indonesian, because so far researcher have only thought that the everyday language used is Indonesian, but after further investigation, in fact many Tangsi languages come from Javanese and Minang languages.